SOME APPROACHES TO BUILDING A KNOWLEDGE BASE ON PHYSICAL EFFECTS USED TO PRESERVE FOOD QUALITY - Shegelman I. R., Vasilyev A. S. (A breakthrough in science: development strategies, 2019)
approaches to formation of knowledge base on physical effects for selection of design and technological solutions for improvement and creation of new types of equipment and technologies used for preservation of food products are considered.
Keywords: пищевые продукты; база знаний; knowledge base; food; physical effects; физические эффекты; консервирование; preservation